Profil Peresepan Penggunaan Obat Gastritis Pada Pasien Rawat Jalan di RSUD Batara Guru Belopa Periode Januari-Maret 2023 - Muris, Dian Indri; Herman, Hendra; hasrawati, A. (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Gastritis is a stomach disease caused by inflammation of the stomach wall. That is why gastritis is often referred to as inflammation of the stomach. The causes of gastric disorders include infection with Helicobacter pylori bacteria, side effects of using non-steroidal anti-inflammatory drugs (NSAIDs), poor lifestyle, and prolonged stress. This study aims to determine the prescription of gastritis drugs in outpatients at Batara Guru Belopa Hospital based on patient characteristics (age and gender), as well as to see the suitability and classification of gastritis drugs which include dose and frequency, drug type parameters, drug combinations, and drug interactions prescribed. The method in this study is descriptive research with retrospective research data type. The sample used in this study used purposive sampling method with sampling based on inclusion criteria where 314 gastritis prescription sheets were obtained. Based on the results obtained, it was found that female patients had a greater percentage than men with 208 prescriptions (66.24%), while the largest age group of gastritis patients was the late adulthood age group with ages 35-54 having the largest percentage of 26.75%. The use of gastritis drugs based on the most prescribed type of single therapy is Omeprazole as many as 79 prescriptions (49.69%), the most prescribed type of two drug combination therapy is Omeprazole and Sucralfat as many as 47 prescriptions (31.97%), and for the type of three drug combination therapy the most prescribed is Omeprazole + Ranitidine + Sucralfat (42.85%).